Structures of Accumulation and Security: Understanding Contemporary Farm Attacks Through Autoethnographic Reflections and Historical Inquiry of the Cape Colony - Botha, Carla (Department of Political Studies, 2025)
This dissertation examines the complex relationship between settler accumulation and security within instances of violence on farms in the Cape Colony, employing a dual methodology of microhistory and autoethnographic inquiry. This study seeks deeper insights into the enduring patterns that characterise settler colonies, particularly in relation to the perception of persecution of the settler group. Through the lens of autoethnography, personal reflections are interwoven with microhistories of the early settler colonial period, revealing the structures that underpin settler security dynamics. By shedding light on historical precedents, the research aims to unravel the contemporary phenomenon of farm attacks. This interdisciplinary approach navigates through time and personal narratives to illuminate the settler colonial structure and its historic, as well as contemporary implications.